Penerapan Modifikasi Perilaku untuk Meningkatkan Kemampuan Memakai Kaos Berlengan pada Anak dengan Disabilitas Intelektual Tingkat Berat - Aisyah Almas Silmina; Efriyani Djuwita (Humanitas (Jurnal Psikologi), 2018)
Self-help capabilities are an important ability to have by individuals to support daily life activities. Usually, entering the school age children are able to perform self-help capabilities independently. Yet, a child with disability intellectual has a tendency to experience difficulties in conducting self-help capabilities activities independently, especially children with severe intellectual disability. Children with intellectual disability with severe level need support in almost everyday activities such as dressing, eating and take a leak. The subject for this research was a girl aged 6 years 7 months who were diagnosed with severe intellectual disability. The purpose of this study is to improve the ability of wearing sleeves independently. This research method is single case AB design. Technique used in this research is backward chaining and positive reinforcement. The research was conducted in 10 sessions consisting of 5 experiments per session. The results of this research indicate that backward chaining techniques can improve the ability to wear sleeves to children with severe intellectual disability.